Assessing shared respiratory pathogens between domestic (Ovis aries) and bighorn (Ovis canadensis) sheep; methods for multiplex PCR, amplicon sequencing, and bioinformatics to characterize respiratory flora. - Karen A Fox; Christopher A W MacGlover; Kevin A Blecha; Mark D Stenglein (PLoS ONE, 2023)
Respiratory disease is responsible for dramatic population declines in bighorn sheep (Ovis canadensis), and respiratory pathogen diagnostics contribute to the management of bighorn populations. To create a comprehensive and consistent approach to bighorn sheep respiratory diagnostics, we created a culture-independent assay to detect and strain type Mannheimia haemolytica, Bibersteinia trehalosi, Pasteurella multocida, and Mycoplasma ovipneumoniae. The assay also detects and characterizes the Pasteurellaceae leukotoxin A gene, and broadly assesses the bacterial composition of each sample based on 16S rRNA sequences. The assay is based on a three-step approach: 1) Multiplex PCR to amplify targets including eight loci for each bacterial species, the Pasteurellaceae lktA gene, and the 16S rRNA gene 2) Library preparation, barcoding, and short-read Illumina sequencing to determine the genetic sequences of each target, and 3) Bioinformatics in the form of automated software to analyze genetic sequences. The assay was designed to assess shared pathogens between domestic and bighorn sheep, but could be useful for many applications in bighorn sheep respiratory disease research and management.